One Dimensional SnO2/ZnO Nanofiber Composite for Dye Sensitized Solar Cell - Zinab, H. Bakr; Qamar, Wali; Rajan, Jose (Universiti Malaysia Pahang, 2016)
One-dimensional nano-morphology SnO2 and composite of ZnO/SnO2 nanofibers were synthesized, and fabricated by electrospinning technique. The materials were characterized by X-ray diffraction (XRD) and scanning electron microscopy (FESEM) techniques to confirm the crystal structure and morphology. Dye-sensitized solar cells (DSSCs) were fabricated using these nanofibers as photoanodes and their performance were compared with to commercial TiO2 paste (P25)-based DSSCs. photoconversion efficiency (PCE) of 4.64 % was realized in composite ZnO/SnO2 nanofibers based DSSCs which comparable to 4.75 % for P25 based DSSCs.